2021
DOI: 10.3390/s21124027
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New Contactless and Continuous Respiratory Rate Monitoring Device Based on Ultra-Wideband Radar Technology

Abstract: Respiratory rate (RR) is typically the first vital sign to change when a patient decompensates. Despite this, RR is often monitored infrequently and inaccurately. The Circadia Contactless Breathing Monitor™ (model C100) is a novel device that uses ultra-wideband radar to monitor RR continuously and un-obtrusively. Performance of the Circadia Monitor was assessed by direct comparison to manually scored reference data. Data were collected across a range of clinical and non-clinical settings, considering a broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…Comparison between studies is always difficult, because the sleep data, reference device or signal processing, and performance metrics are different. However, to the best of our knowledge, the results of this study are significantly better than those of other technologies [23][24][25][44][45][46] including radar technology [27,29]. The validated measurements are also more instantaneous, as previous studies have averaged RRs over epochs of data.…”
Section: Comparison With Previous Studiesmentioning
confidence: 71%
See 2 more Smart Citations
“…Comparison between studies is always difficult, because the sleep data, reference device or signal processing, and performance metrics are different. However, to the best of our knowledge, the results of this study are significantly better than those of other technologies [23][24][25][44][45][46] including radar technology [27,29]. The validated measurements are also more instantaneous, as previous studies have averaged RRs over epochs of data.…”
Section: Comparison With Previous Studiesmentioning
confidence: 71%
“…Radar technology has been extensively studied for measuring RR [26][27][28][29] and even for detecting apnea [26,[30][31][32]. However, most studies have measured RR only during optimized conditions where the participant is asked to sit or lie still [26] or during natural movements or sleep, but only for short periods [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One [42] In the group of studies assessing contactless devices, 22 devices utilised electromagnetic radiation at a variety of spectral wavelengths to derive vital signs. One of these was a commercially available device [43] (Circadia Health, London, UK) [43]. There were seven studies assessing under-mattress sensors, three of which were with a commercially available device (Earlysense, Earlysense Inc, Woburn, MA, USA) [13,44,45].…”
Section: Resultsmentioning
confidence: 99%
“…Novel and dedicated UWB sensor and system electronics for a variety of applications were investigated, tested, and optimized in [4,5]. In [4], the authors presented the validation of a new commercial contactless and continuous respiratory rate monitoring device; validation was carried out by direct comparison to manually scored reference data in a total of 50 subjects. It was shown that the accuracy rate reached 90%.…”
mentioning
confidence: 99%